ANALYSIS OF STUDENTS' SELF AWARENESS IN MEDIATING THE INFLUENCE OF MANAGEMENT INFORMATION SYSTEMS AND ACTION CARD SYSTEMS ON REINFORCEMENT OF LEARNING - Azhari, M. Fadli Al; Effendi, Mukhlison (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Self-awareness helps students understand their own strengths, weaknesses, interests, and learning styles. With better self-understanding, students can use management information systems and action cards more effectively according to their learning needs. This research aims to explore the role of self-awareness as a mediator of influence between management information systems, action card systems, and learning reinforcement. The survey method was used to collect data based on purposive sampling from 64 MA Darul Huda Ponorogo students. Data collection was carried out using a questionnaire consisting of a Likert scale with 4 alternative answers. PLS-SEM analysis was used to analyze data and test the conceptual model. The results of the analysis show that the management information system has no significant effect on self-awareness and learning reinforcement. In addition, self-confidence was proven not to mediate the effect of management information systems on strengthening learning. These findings highlight the importance of self-awareness in facilitating the development of reinforced learning through management information systems and participation in action card systems. The practical implication of this research is the need for the role of classmates in strengthening learning, which does not only focus on aspects of teacher support, but also on aspects of self-reflection. Research supports efforts to design professional development programs that strengthen student self-awareness and integrate management information systems and action card systems as effective strategies for enhancing learning reinforcement.